The Underground Galleries in the City of Cahul „Even Today They Remain an Enigma” - Aliona GRATI; Ion GHELEȚCHI (Dialogica: Revistă de Studii Culturale și Literatură, 2022)
e dialogue takes place on the sidelines of one of the most interesting discoveries of recent years in the area of the old city of Cahul. Ion Ghelețchi, doctor in history, associate professor and vice-rector at the State University “B.P. Hasdeu” from Cahul, reveals his experience of archaeological research on the underground galleries, recently discovered in the city of Cahul, exposing his hypotheses regarding the period in which they were built, as well as how they were used. These underground galleries are usually located at a depth varying between 3 and 7m. They are in the form of a tunnel about 1.70 and 1.80 m high, lined with almost perfectly laid burnt bricks, having a semi-cylindrical vault. The material for making bricks it is clay mixed with sand. Some galleries served as warehouses for storing food and various beverages, others for storing fish and storing ice. The most circulated legend in the region in relation to these underground galleries is that there would be a passage from Cahul, under the Prut river, which would come out on the town of Oancea (Romania). The historical truth of these tunnels remains a research topic for the future.